(untitled) - Frank B Salisbury (Belmont, California, 1991)
The book provides a explanation of the physiology of plants from see germination to vegetative growth, maturation, and flowering. Section One presents physical processes that go on in plants, including the structures of plant cells. Section Two concerns the biochemical processes, including photosynthesis. Section Three describes plant growth and development, including molecular biology and genetic engineering. Section Four describes important environmental factors, including environmetal physiology and stress physiology. The book also has added three appendices. Appendix A describes SI units of measurement. Appendix B covers properties of various kinds of radiation. Appendix C summarizes transcription and translation
Keywords: plant physiology